A study of selected British and European flint assemblages of Late Devensian and Early Flandrian Age - Barton, RNE (1986)
﻿ This dissertation is concerned with the analysis of selected blade assemblages from Late Devensian and Early Flandrian contexts in Southern Britain (c. 12,500 - 9,000 BP). The British sites studied are divided into three main groupings: Upper Palaeolithic, Long Blade, and Mesolithic, each of which contains material of a typologically and technologically distinct nature. Despite previous important studies in the British Upper Palaeolithic and Mesolithic, no major work until now has been undertaken on the third technology, that of the Long Blade sites, which seems to occupy a chronological position intermediate between the other two. The dissertation incorporates the first comprehensive description of material from Long Blade sites and contrasts it with the sets of artefacts from the other two groups. Comparative data from the Upper Palaeolithic and Mesolithic derive mainly from primary information recovered in two excavations directed by myself at Hengistbury Head between 1980-4. The chapters consider the archaeological material in chronological order beginning in Chapter 1 with the Late Upper Palaeolithic assemblage from Hengistbury Head. Chapters 2 and 3 are devoted to the Long Blade assemblages from Britain and Northwestern Europe, whilst in the fourth chapter the Early Mesolithic material from Hengistbury and related sites in Southern Britain is considered. The fifth and last chapter is given over to discussion and final conclusions. Appended to the last chapter is a gazetteer of 159 specified Long Blade findspots in Southern Britain, the first time this material has ever been gathered together. Explanatory notes and a key are provided at the front of the Gazetteer. In studying the artefacts I have laid particular emphasis on technology as well as typology, and in studying technology I have been particularly influenced by my own work on the experimental manufacture and use of implements. Given that my two excavated sites were very little disturbed, I have also been able to make major use of conjoining artefacts, not only as an aid to understanding the differing techniques of artefact manufacture, but also in interpreting the archaeology of the sites. Some use was also made of experimental taphonomy. These aspects of my work are referred to in the text, notably in Chapters 1 and 4.